Physicochemical and sensory quality of breakfast cereals produced from flour blends of maize and pigeon pea - Clement Chinedum Ezegbe; Smith G. Nkhata; Ekpeno Sunday Ukpong; Mary Chikodili Ezeh; Kalu Sunday Okocha; Bernard Femi Pedro (Heliyon)
Breakfast cereals offer affordable, quick and convenient meal options. This study examined the proximate, techno-functional, mineral and sensory qualities of breakfast cereals produced from a flour blend of maize and pigeon peas. Maize flour was substituted with pigeon pea flour at 0 %, 10 %, 20 %, 30 %, 40 % and 50 % levels. The composite flours (100 g), sugar (25 g), salt (5 g) and water (50 ml) were mixed to form a paste, baked at 110 °C for 1 h then cooled. The proximate composition, techno-functional properties, minerals and sensory quality were evaluated. With increase in pigeon pea flour incorporation, there were increase in crude protein from 10.93 to 14.30 %, ash from 1.56 to 3.11 % while crude fibre from 1.25 to 3.37 %. In contrast, there was significant (p < 0.05) decrease in water absorption capacity from 361.30 to 181.83 %. With 50 % pigeon pea flour incorporation, calcium significantly increased from 27.95 to 44.55 mg/100g while iron and magnesium decreased from 3.92 to 2.16 mg/100g and 75.07 to 63.16 mg/100g, respectively. Breakfast cereal containing maize:pigeon pea flour in the ratio 80:20 and 70:30 generally had the highest mean sensory scores on a 7-point Hedonic scale. This suggests that maize flour can be substituted with pigeon pea up to 30 % without producing significant changes in the sensory quality.